Relationship between employment changes and psychosocial discomfort during the COVID-19 pandemic - Solís-Soto, María Teresa; Burrone, María Soledad; Basagoitia, Armando; Rojas, Luna; Valenzuela, Paulina; Barrientos, Catalina; Molina, Fabiola; Valdés, Daniela; Arrosi, Silvina; Ramos, Silvina; Rincón, Paulina; Valenzuela, Loreto Villagran (International Journal of Public Health Science (IJPHS), 2025)
Due to the COVID-19 pandemic and the containment and prevention measures established at the global and national level, daily life activities were affected, deepening inequities in Chile and impacting the population's mental health. The study's objective was to analyze the relationship between working conditions and psychological distress during the COVID-19 pandemic in Chile. For this, a cross-sectional study was implemented using an anonymous and self-administered online questionnaire, reaching a final sample size of 784 people ≥18 years. The questionnaire explored sociodemographics, work, income, and psychological distress information. We computed logistic regression models to assess risk factors associated with psychological discomfort. Data showed that higher percentage of women dedicate more hours per week to household chores, caring for other people, and accompanying schoolwork than men. More than half of the participants (55%) reported psychological discomfort, with household income reduction as the main risk factor. Our results reflect the impact of the COVID-19 pandemic in Chile, with a severe decrease in household income, a risk factor for psychological discomfort. It is important to implement strategies to protect mental health during health emergencies, considering more vulnerable populations.